Controlling Californian thistle (Cirsium arvense) through pasture management - Eerens, J.P.J.; Seefeldt, S.S.; Garry, G.; Armstrong, M.L. (New Zealand Plant Protection, 2002)
The impact of grazing pasture to different heights on the development of Californian thistle (Cirsium arvense) was simulated over two years in container trials Californian thistle field densities were simulated by transplanting seedlings into perennial ryegrass (Lolium perenne) and white clover (Trifolium repens) that had been sown at 20 and 5 kg/ha respectively In a high fertility situation adding fertiliser did not influence Californian thistle development in the pasture sward Californian thistle grown without companion ryegrass and white clover grew the best reaching the highest levels of biomass (shoot and root material) and number of shoots (supra and subterranean) Californian thistle grown with the highest level of pasture competition fared the worst with the lowest level of biomass and number of shoots The results show that grazing to a higher residual severely reduces Californian thistle growth and is a useful tool to assist in the control of Californian thistle